Nano hard chromium accelerant as well as preparation method and application thereof

By using nano hard chromium accelerator to improve the hardness and wear resistance of the plating layer in hard chromium electroplating, the problems of low production efficiency and unsatisfactory hardness of existing chromium plating additives when electroplating hydraulic cylinders, hydraulic oil rods and other products are solved, and a more efficient plating process and excellent plating quality are achieved.

CN119776921APending Publication Date: 2025-04-08GUANGDONG SHAOPEI POWER MASCH CO LTD +1
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202411938853.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

When used in electroplating of hydraulic cylinders, hydraulic oil rods and other products, existing chrome plating additives have problems such as low production efficiency, hardness and wear resistance do not meet product requirements, and customers are not satisfied with the appearance of the product.

Method used

The nanohard chromium accelerator prepared uniformly by mixing the first solution, the second solution, the third solution, the fourth solution and the fifth solution are used to improve the hardness and wear resistance of the plating layer through its application in hard chromium electroplating.

Benefits of technology

The deposition speed is accelerated, the current efficiency is improved, the coating is crystallized and smooth, the hardness and wear resistance of the coating are improved, and the production time and cost are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776921A_ABST
    Figure CN119776921A_ABST
Patent Text Reader

Abstract

The invention relates to a nano hard chromium accelerant as well as a preparation method and application thereof. The nano hard chromium accelerant is obtained by uniformly mixing a first solution, a second solution, a third solution, a fourth solution and a fifth solution, the first solution comprises 40-80 g of a first mixture and 60 wt% of deionized water, and the first mixture comprises sodium benzenesulfinate, sodium thiosulfate and 60 wt% of deionized water, wherein the mass ratio of sodium benzenesulfinate to sodium thiosulfate is 2: 1; the second solution comprises 10-50 g of benzenesulfonic acid and 60 wt% of deionized water; the third solution comprises 2-8 g of tartaric acid and 60 wt% of deionized water; the fourth solution is prepared from 1g to 5g of alkylphenol polyoxyethylene ether and 60wt% of deionized water; the fifth solution comprises 0.5-3 g of a second mixture and 60 wt% of a 50 vol% ethanol solution, the second mixture comprises nano cobalt sulfate and nano silicon carbide in a mass ratio of 1: 1, and the particle size is 30-50 nm. By using the hard chromium accelerant disclosed by the invention, the deposition speed can be increased, the current efficiency can be improved, three wires can be produced per hour at the initial electroplating stage, fine and smooth crystal of a plating layer is ensured, and the hardness of the plating layer is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electroplating, and in particular to a nano hard chromium accelerator and a preparation method and application thereof. Background Art

[0002] Hard chrome plating is a process for plating a layer of chromium on the surface of various substrates in a plating solution containing chromic anhydride (CrO3), sulfuric acid and water. Through hard chrome plating, the substrate surface can have the advantages of high hardness, good wear resistance, corrosion resistance, and beautiful appearance.

[0003] Hard chrome electroplating of complex structured parts brings new challenges to the electroplating process. It requires the coating to have better dispersion ability, better deep plating ability, better bonding strength and take as short a time as possible during the electroplating process. To this end, researchers have developed a chrome plating additive composed of organic acid salts, organic acids, buffers and wetting agents. This chrome plating additive can improve the deep plating ability of the coating and is suitable for hard chrome electroplating of workpieces with complex structures.

[0004] However, the inventors have found through practice that when the current chrome plating additives are used for electroplating of products such as hydraulic cylinders and hydraulic oil rods, since hydraulic cylinders and hydraulic oil rods usually have a certain length and pay more attention to indicators related to the service life of the product, such as the thickness, hardness, wear resistance and corrosion resistance of the coating, the existing chrome plating additives are not effective in improving the thickness, hardness and wear resistance of the coating. It takes a long time to achieve a thicker thickness, and there is a problem of low production efficiency. There is also a problem that the hardness and wear resistance do not meet the product requirements, and there is also a problem that customers are not satisfied with the appearance of the product. Summary of the invention

[0005] Based on this, the object of the present invention is to provide a nano hard chromium accelerator and a preparation method and application thereof, which is obtained by uniformly mixing a first solution, a second solution, a third solution, a fourth solution and a fifth solution;

[0006] The first solution includes 40 g to 80 g of a first mixture and 60 wt % of deionized water, wherein the first mixture includes sodium benzenesulfinate and sodium thiosulfate in a mass ratio of 2:1;

[0007] The second solution includes 10 g to 50 g of benzenesulfonic acid and 60 wt % of deionized water;

[0008] The third solution comprises 2 g to 8 g of tartaric acid and 60 wt % of deionized water;

[0009] The fourth solution comprises 1 g to 5 g of alkylphenol polyoxyethylene ether and 60 wt % of deionized water;

[0010] The fifth solution comprises 0.5 g to 3 g of the second mixture and 60 wt % of an ethanol solution, wherein the concentration of the ethanol solution is 50 vol %, and the second mixture comprises nano cobalt sulfate and nano silicon carbide in a mass ratio of 1:1, and the particle size of the nano cobalt sulfate and the particle size of the nano silicon carbide are 30 nm to 50 nm. The hard chrome accelerator of the present invention can accelerate the deposition speed and improve the current efficiency, which can reach 3 wires per hour in the initial stage of electroplating, and also ensure that the coating crystallization is fine and smooth, and improve the hardness of the coating.

[0011] The technical solution of the present invention is achieved by the following methods:

[0012] A nano hard chrome accelerator is obtained by uniformly mixing a first solution, a second solution, a third solution, a fourth solution and a fifth solution;

[0013] The first solution includes 40 g to 80 g of a first mixture and 60 wt % of deionized water, wherein the first mixture includes sodium benzenesulfinate and sodium thiosulfate in a mass ratio of 2:1;

[0014] The second solution includes 10 g to 50 g of benzenesulfonic acid and 60 wt % of deionized water;

[0015] The third solution comprises 2 g to 8 g of tartaric acid and 60 wt % of deionized water;

[0016] The fourth solution comprises 1 g to 5 g of alkylphenol polyoxyethylene ether and 60 wt % of deionized water;

[0017] The fifth solution includes 0.5g to 3g of the second mixture and 60wt% ethanol solution, the concentration of the ethanol solution is 50vol%, the second mixture includes nano-cobalt sulfate and nano-silicon carbide in a mass ratio of 1:1, and the particle size of the nano-cobalt sulfate and the particle size of the nano-silicon carbide are 30nm to 50nm.

[0018] The use of the hard chrome accelerator of the present invention can accelerate the deposition speed and improve the current efficiency, which can reach 3 threads per hour in the initial stage of electroplating. It also ensures that the crystallization of the coating is fine and smooth, and improves the hardness of the coating. Among them, the first mixture of the present invention mainly plays a role in reducing the resistivity and improving the current efficiency in the nano hard chrome accelerator, which is about 30% to 40% higher than the current efficiency of the common chromium additive organic acid salt (one or more of sodium sulfonate, sodium acetate, sodium aminosulfonate, sodium aminoacetate, and sodium monocitrate); benzenesulfonic acid mainly has a chelating effect; tartaric acid buffer mainly has a stabilizing effect on regulating the comprehensive pH value in the nano hard chrome accelerator; OP-10 as a buffer has good uniformity of promoting the coating, better emulsification and wetting tank liquid, and excellent antistatic properties; nano-scale cobalt sulfate and silicon carbide powder (particle size in the range of 30 to 50nm) can greatly improve the hardness and friction and wear resistance of the coating. The hardness and friction and wear resistance of the coating prepared by the hard chrome accelerator of the present invention are more than 30% higher than the hardness of the coating prepared by the existing chrome plating additives;

[0019] The invention uses a new organic acid salt, an organic acid, a buffer, a wetting agent and a corresponding nano-level hard material to prepare a nano-hard chromium accelerator for improving the current efficiency and hardness of the plating layer. The invention not only has a simple preparation process, but also has a simple raw material formula and a wide range of uses. The invention can meet the requirements of hard chromium plating of the inner and outer cavities of workpieces in many fields (piston rods, hydraulic cylinders, bearings and other miscellaneous parts) and can obtain excellent electroplating quality. At the same time, the deposition speed is increased, the electroplating time is greatly shortened, and the electroplating time can reach 3 threads per hour in the initial stage of electroplating, thereby reducing the cost. The plating layer is prevented from having large cracks, and the number of microcracks is 400-1000 per centimeter, and the physical protection performance is excellent. The plating layer has excellent toughness and can effectively prevent the chromium layer from peeling in the high current area. The plating layer has fine crystals and the hardness can reach more than 1200 HV. The process has simple requirements on equipment, stable performance, simple operation and easy maintenance.

[0020] Furthermore, the mass of the first mixture is 55g-70g, the mass of the benzenesulfonic acid is 20g-40g, the mass of the tartaric acid is 3.5g-6.5g, the mass of the alkylphenol polyoxyethylene ether is 1g-3g, and the mass of the second mixture is 0.5g-2.5g.

[0021] Furthermore, the mass of the first mixture is 65g-70g, the mass of the benzenesulfonic acid is 20g-25g, the mass of the tartaric acid is 5g-6.5g, the mass of the alkylphenol polyoxyethylene ether is 2g-3g, and the mass of the second mixture is 1.5g-2.5g.

[0022] Furthermore, the mass of the first mixture is 65g, the mass of the benzenesulfonic acid is 25g, the mass of the tartaric acid is 6g, the mass of the alkylphenol polyoxyethylene ether is 2g, and the mass of the second mixture is 2g. The nano hard chrome accelerator of this ratio has an ideal effect.

[0023] Furthermore, the mass of the first mixture is 70g, the mass of the benzenesulfonic acid is 20.5g, the mass of the tartaric acid is 5g, the mass of the alkylphenol polyoxyethylene ether is 3g, and the mass of the second mixture is 1.5g. The nano hard chrome accelerator of this ratio has an ideal effect.

[0024] The present invention also provides a method for preparing any of the above-mentioned nano hard chromium accelerators, comprising the following steps:

[0025] Weigh 40 wt% of the first mixture according to the ratio and add it into 60 wt% of deionized water to fully dissolve and stir evenly to obtain a first solution;

[0026] Weigh 40 wt % of benzenesulfonic acid according to the ratio and add it to 60 wt % of deionized water to fully dissolve and stir evenly to obtain a second solution;

[0027] Weigh 40 wt % of tartaric acid according to the ratio and add it into 60 wt % of deionized water to fully dissolve and stir evenly to obtain a third solution;

[0028] Weigh 40 wt % of alkylphenol polyoxyethylene ether according to the ratio and add it into 60 wt % of deionized water to fully dissolve and stir evenly to obtain a fourth solution;

[0029] Weigh 40 wt % of the second mixture according to the ratio and add it into a 60 wt % ethanol solution to fully dissolve and stir evenly to obtain a fifth solution with a pH value between 9 and 10;

[0030] The first solution, the second solution, the third solution, the fourth solution and the fifth solution are mixed and stirred uniformly to obtain a nano hard chromium accelerator.

[0031] The present invention also provides an application of any of the above-mentioned nano hard chrome accelerators, which is applied to hard chrome electroplating.

[0032] Furthermore, the application method comprises the following steps: adding the nano hard chrome accelerator into a hard chrome plating tank filled with a hard chrome plating solution.

[0033] Furthermore, the dosage of the nano hard chromium accelerator is 30 ml / L.

[0034] Furthermore, the hard chrome plating solution includes chromic anhydride, trivalent chromium and sulfuric acid.

[0035] For better understanding and implementation, the present invention is described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a schematic diagram of the experimental device of the nine-grid Hastelloy slot test piece experiment of the present invention;

[0037] Figure 2 This is a schematic diagram of the back side of the Hastelloy disc after the nine-grid Hastelloy groove test piece experiment is carried out in Example 1 of the present invention;

[0038] Figure 3 This is a front view schematic diagram of the Hastelloy disc after the nine-grid Hastelloy groove test piece experiment of Example 1 of the present invention;

[0039] Figure 4 This is a schematic diagram of the product described in Example 1 of the present invention under a 100x microscope;

[0040] Figure 5 This is a schematic diagram of the back side of the Hastelloy disc after the nine-grid Hastelloy groove test piece experiment of Example 2 of the present invention;

[0041] Figure 6 This is a front view schematic diagram of the Hastelloy disc after the nine-grid Hastelloy groove test piece experiment of Example 2 of the present invention;

[0042] Figure 7 This is a schematic diagram of the product described in Example 2 of the present invention under a microscope at 100 times magnification;

[0043] Figure 8 This is a schematic diagram of the back side of the Hastelloy disc after the nine-grid Hastelloy groove test piece experiment of Example 3 of the present invention;

[0044] Fig. 9 This is a front view schematic diagram of the Hastelloy disc after the nine-grid Hastelloy groove test piece experiment of Example 3 of the present invention;

[0045] Fig.10 This is a schematic diagram of the product described in Example 3 of the present invention under a microscope at 100 times magnification;

[0046] Fig.11 This is a schematic diagram of the back side of the Hastelloy plate after the nine-grid Hastelloy groove test piece experiment is carried out in Example 4 of the present invention;

[0047] Fig.12 This is a front view schematic diagram of the Hastelloy disc after the nine-grid Hastelloy groove test piece experiment of Example 4 of the present invention;

[0048] Fig.13 This is a schematic diagram of the product described in Example 4 of the present invention under a 100x microscope;

[0049] Fig.14 This is a schematic diagram of the back side of the Hastelloy plate after the nine-grid Hastelloy groove test piece experiment of Comparative Example 1 of the present invention;

[0050] Fig.15 This is a front view of the Hastelloy disc after the nine-grid Hastelloy groove test piece experiment of Comparative Example 1 of the present invention;

[0051] Fig.16 This is a schematic diagram of the product described in Comparative Example 1 of the present invention under a 100x microscope;

[0052] Among them, there are experimental aqueduct 1, anode fixing plate 2, and cathode fixing plate 3. DETAILED DESCRIPTION

[0053] It should be clear that the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the embodiments of the present application.

[0054] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the embodiments of the present application. The singular forms of "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.

[0055] When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present application. On the contrary, they are merely examples of devices and methods consistent with some aspects of the present application as detailed in the attached claims. In the description of the present application, it should be understood that the terms "first", "second", "third", etc. are only used to distinguish similar objects, and do not have to be used to describe a specific order or sequence, nor can they be understood as indicating or implying relative importance. For those of ordinary skill in the art, the specific meanings of the above terms in the present application can be understood according to the specific circumstances.

[0056] In addition, in the description of this application, unless otherwise specified, "plurality" means two or more. "And / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0057] It should be understood that the embodiments of the present application are not limited to the precise structures described above and shown in the drawings, and various modifications and changes can be made without departing from the scope thereof. The scope of the embodiments of the present application is limited only by the appended claims.

[0058] As an embodiment of the present invention, this embodiment provides a nano hard chromium accelerator, which is obtained by uniformly mixing a first solution, a second solution, a third solution, a fourth solution and a fifth solution;

[0059] The first solution includes 40 g to 80 g of a first mixture and 60 wt % of deionized water, wherein the first mixture includes sodium benzenesulfinate and sodium thiosulfate in a mass ratio of 2:1;

[0060] The second solution includes 10 g to 50 g of benzenesulfonic acid and 60 wt % of deionized water;

[0061] The third solution comprises 2 g to 8 g of tartaric acid and 60 wt % of deionized water;

[0062] The fourth solution comprises 1 g to 5 g of alkylphenol polyoxyethylene ether and 60 wt % of deionized water;

[0063] The fifth solution includes 0.5g to 3g of the second mixture and 60wt% ethanol solution, the concentration of the ethanol solution is 50vol%, the second mixture includes nano-cobalt sulfate and nano-silicon carbide in a mass ratio of 1:1, and the particle size of the nano-cobalt sulfate and the particle size of the nano-silicon carbide are 30nm to 50nm.

[0064] Furthermore, the mass of the first mixture is 55g-70g, the mass of the benzenesulfonic acid is 20g-40g, the mass of the tartaric acid is 3.5g-6.5g, the mass of the alkylphenol polyoxyethylene ether is 1g-3g, and the mass of the second mixture is 0.5g-2.5g.

[0065] Furthermore, the mass of the first mixture is 65g-70g, the mass of the benzenesulfonic acid is 20g-25g, the mass of the tartaric acid is 5g-6.5g, the mass of the alkylphenol polyoxyethylene ether is 2g-3g, and the mass of the second mixture is 1.5g-2.5g.

[0066] Furthermore, the mass of the first mixture is 65 g, the mass of the benzenesulfonic acid is 25 g, the mass of the tartaric acid is 6 g, the mass of the alkylphenol polyoxyethylene ether is 2 g, and the mass of the second mixture is 2 g.

[0067] Furthermore, the mass of the first mixture is 70 g, the mass of the benzenesulfonic acid is 20.5 g, the mass of the tartaric acid is 5 g, the mass of the alkylphenol polyoxyethylene ether is 3 g, and the mass of the second mixture is 1.5 g.

[0068] The present invention also provides a method for preparing any of the above-mentioned nano hard chromium accelerators, comprising the following steps:

[0069] Weigh 40 wt% of the first mixture according to the ratio and add it into 60 wt% of deionized water to fully dissolve and stir evenly to obtain a first solution;

[0070] Weigh 40 wt % of benzenesulfonic acid according to the ratio and add it to 60 wt % of deionized water to fully dissolve and stir evenly to obtain a second solution;

[0071] Weigh 40 wt % of tartaric acid according to the ratio and add it into 60 wt % of deionized water to fully dissolve and stir evenly to obtain a third solution;

[0072] Weigh 40 wt % of alkylphenol polyoxyethylene ether according to the ratio and add it into 60 wt % of deionized water to fully dissolve and stir evenly to obtain a fourth solution;

[0073] Weigh 40 wt % of the second mixture according to the ratio and add it into a 60 wt % ethanol solution to fully dissolve and stir evenly to obtain a fifth solution with a pH value between 9 and 10;

[0074] The first solution, the second solution, the third solution, the fourth solution and the fifth solution are mixed and stirred uniformly to obtain a nano hard chromium accelerator.

[0075] The present invention also provides an application of any of the above-mentioned nano hard chrome accelerators, which is applied to hard chrome electroplating.

[0076] Furthermore, the application method comprises the following steps: adding the nano hard chrome accelerator into a hard chrome plating tank filled with a hard chrome plating solution.

[0077] Furthermore, the dosage of the nano hard chromium accelerator is 30 ml / L.

[0078] Furthermore, the hard chrome plating solution includes chromic anhydride, trivalent chromium and sulfuric acid.

[0079] The physical properties and test methods of the embodiments or comparative examples of the present invention are as follows:

[0080] The hardness is tested using a MIC 10 hardness tester imported from Germany (display range: 0-9999 measurement range: 20-1740 HV).

[0081] The steps of the nine-square Hastelloy slot test are as follows: Figure 1 , the chromium anode is clamped and fixed on the anode fixing plate 2 of the experimental aqueduct 1 by a conductive clamp electrically connected to the positive electrode of the rectifier, and the Hastelloy plate is clamped and fixed on the cathode fixing plate 3 of the experimental aqueduct 1 by a conductive clamp electrically connected to the negative electrode of the rectifier, wherein the cathode fixing plate 3 is provided with nine holes distributed in a nine-square grid, and a 60°C plating solution uniformly mixed with a chromium plating additive / a plating solution uniformly mixed with a nano-hard chromium accelerator is added into the experimental aqueduct 1 until the plating solution covers the nine holes of the cathode fixing plate 3, and then power is turned on, and electroplating is carried out at 9A for 3 minutes, wherein the concentration of chromic anhydride in the plating solution is 242g / L, the concentration of trivalent chromium is 7.2g / L, the concentration of sulfuric acid is 2.5g / L, and the addition amount of the chromium plating additive / nano-hard chromium accelerator is 30ml / L. It should be noted that the nine-square Hastelloy slot test is a relatively rigorous test, the purpose of which is to reflect the improvement in the performance of the nano-hard chromium accelerator of the present invention. The presence of defects in the results of the nine-square Hastelloy slot test does not mean that there will be defects in the product during actual production.

[0082] It should be noted that the proportions described in the embodiments of the present invention or comparative examples are all weight percentages. The components and contents of each layer in the embodiments of the present invention and comparative examples are shown in Table 1 below.

[0083] Table 1

[0084] Components Example 1 Example 2 Example 3 Example 4 First mixture (g) 55 70 65 68 Benzenesulfonic acid(g) 40 20.5 25 20 Tartaric acid(g) 3.5 5 6 6.5 OP-10(g) 1 3 2 3 Second mixture (g) 0.5 1.5 2 2.5

[0085] Example 1

[0086] This embodiment provides a nano hard chromium accelerator, which is obtained by uniformly mixing a first solution, a second solution, a third solution, a fourth solution and a fifth solution. The preparation method includes the following steps:

[0087] Weigh 55 g of the first mixture according to a mass ratio of sodium benzenesulfinate: sodium thiosulfate = 2:1, and weigh 66 g of deionized water, pour the first mixture into a beaker containing 66 g of deionized water, and stir well to obtain a first solution;

[0088] Weigh 40 g of benzenesulfonic acid and 48 g of deionized water, pour the benzenesulfonic acid into a beaker containing 48 g of deionized water, and stir well to obtain a second solution;

[0089] Weigh 3.5 g of tartaric acid and 5.3 g of deionized water, pour the tartaric acid into a beaker containing 5.3 g of deionized water, and stir well to obtain a third solution;

[0090] Weigh 1 g of alkylphenol polyoxyethylene ether (OP-10) and 1.5 g of deionized water, pour the alkylphenol polyoxyethylene ether into a beaker containing 1.5 g of deionized water, and stir well to obtain a fourth solution;

[0091] Weigh 0.5 g of the second mixture according to a mass ratio of cobalt sulfate (particle size of 30 nm to 50 nm): silicon carbide (particle size of 30 nm to 50 nm) = 1:1, and weigh 16 ml of a 50 vol% ethanol solution, pour the second mixture into a beaker containing 16 ml of the 50 vol% ethanol solution, and stir well to obtain a fifth solution with a pH value of 9 to 10;

[0092] Pour the first solution, the second solution, the third solution, the fourth solution and the fifth solution into the same beaker and stir evenly to obtain about 194 ml of nano hard chromium accelerator.

[0093] Take the nano-hard chrome accelerator of this example to carry out the nine-square Hastelloy slot test piece experiment. For the experimental results, please refer to Figure 2 and Figure 3 In this embodiment, there are only three positions on the back of the Hastelloy plate without coating, and the coating dispersion distance on the front of the Hastelloy plate is relatively long, and there is a small black surface at the end of the coating dispersion.

[0094] The nano-hard chrome accelerator of this embodiment was used to perform hard chrome electroplating on the hydraulic oil rod product. The electroplating conditions were as follows: (bath solution: chromic anhydride 250 g / L, trivalent chromium 3 g / L, sulfuric acid 2.6 g / L; temperature: 52°C; nano-hard chrome accelerator addition amount: 30 ml / L; current: 4653 A; time: 150 min); during the electroplating process, the current, voltage, coating thickness, etc. were recorded. After the electroplating was completed, a 100x microscope was used for observation. The results are shown in Tables 2 and Figure 4 , the coating of the product produced in this embodiment meets the quality requirements.

[0095] Example 2

[0096] This embodiment provides a nano hard chromium accelerator, which is obtained by uniformly mixing a first solution, a second solution, a third solution, a fourth solution and a fifth solution. The preparation method includes the following steps:

[0097] Weigh 70 g of the first mixture according to a mass ratio of sodium benzenesulfinate: sodium thiosulfate = 2:1, and weigh 84 g of deionized water, pour the first mixture into a beaker containing 84 g of deionized water, and stir well to obtain a first solution;

[0098] Weigh 20.5 g of benzenesulfonic acid and 25 g of deionized water, pour the benzenesulfonic acid into a beaker containing 25 g of deionized water, and stir well to obtain a second solution;

[0099] Weigh 5 g of tartaric acid and 6 g of deionized water, pour the tartaric acid into a beaker containing 6 g of deionized water, and stir well to obtain a third solution;

[0100] Weigh 3 g of alkylphenol polyoxyethylene ether (OP-10) and 3.6 g of deionized water, pour the alkylphenol polyoxyethylene ether into a beaker containing 3.6 g of deionized water, and stir well to obtain a fourth solution;

[0101] Weigh 1.5 g of the second mixture according to a mass ratio of cobalt sulfate (particle size of 30 nm to 50 nm): silicon carbide (particle size of 30 nm to 50 nm) = 1:1, and weigh 48 ml of a 50 vol% ethanol solution, pour the second mixture into a beaker containing 48 ml of the 50 vol% ethanol solution, and stir well to obtain a fifth solution with a pH value of 9 to 10;

[0102] The first solution, the second solution, the third solution, the fourth solution and the fifth solution were poured into the same beaker and stirred evenly to obtain about 223 ml of nano hard chromium accelerator.

[0103] Take the nano-hard chrome accelerator of this example to carry out the nine-square Hastelloy slot test piece experiment. For the experimental results, please refer to Figure 5 and Figure 6 In this embodiment, there are only three positions on the back of the Hastelloy plate without coating, and the coating dispersion distance on the front of the Hastelloy plate is relatively long, and there is a small black surface at the end of the coating dispersion.

[0104] The nano-hard chrome accelerator of this embodiment was used to perform hard chrome electroplating on the hydraulic oil rod product. The electroplating conditions were as follows: (bath solution: chromic anhydride 250 g / L, trivalent chromium 3 g / L, sulfuric acid 2.6 g / L; temperature: 52°C; nano-hard chrome accelerator addition amount: 30 ml / L; current: 4653 A time: 150 min); during the electroplating process, the current, voltage, coating thickness, etc. were recorded. After the electroplating was completed, a 100x microscope was used for observation. The results are shown in Tables 2 and Figure 7 , the coating of the product produced in this embodiment meets the quality requirements.

[0105] Example 3

[0106] This embodiment provides a nano hard chromium accelerator, which is obtained by uniformly mixing a first solution, a second solution, a third solution, a fourth solution and a fifth solution. The preparation method includes the following steps:

[0107] Weigh 65 g of the first mixture according to a mass ratio of sodium benzenesulfinate: sodium thiosulfate = 2:1, and weigh 78 g of deionized water, pour the first mixture into a beaker containing 78 g of deionized water, and stir well to obtain a first solution;

[0108] Weigh 25 g of benzenesulfonic acid and 30 g of deionized water, pour the benzenesulfonic acid into a beaker containing 30 g of deionized water, and stir well to obtain a second solution;

[0109] Weigh 6 g of tartaric acid and 7.2 g of deionized water, pour the tartaric acid into a beaker containing 7.2 g of deionized water, and stir well to obtain a third solution;

[0110] Weigh 2 g of alkylphenol polyoxyethylene ether (OP-10) and 2.4 g of deionized water, pour the alkylphenol polyoxyethylene ether into a beaker containing 2.4 g of deionized water, and stir well to obtain a fourth solution;

[0111] Weigh 2 g of the second mixture according to a mass ratio of cobalt sulfate (particle size of 30 nm to 50 nm): silicon carbide (particle size of 30 nm to 50 nm) = 1:1, and weigh 64 ml of a 50 vol% ethanol solution, pour the second mixture into a beaker containing 64 ml of the 50 vol% ethanol solution, and stir well to obtain a fifth solution with a pH value of 9 to 10;

[0112] The first solution, the second solution, the third solution, the fourth solution and the fifth solution are poured into the same beaker and stirred evenly to obtain a nano hard chromium accelerator.

[0113] Take the nano-hard chrome accelerator of this example to carry out the nine-square Hastelloy slot test piece experiment. For the experimental results, please refer to Figure 8 and Fig. 9 In this embodiment, there are only three positions on the back of the Hastelloy plate without coating, and the coating dispersion distance on the front of the Hastelloy plate is relatively long, and there is a small black surface at the end of the coating dispersion.

[0114] The nano-hard chrome accelerator of this embodiment was used to perform hard chrome electroplating on the hydraulic oil rod product. The electroplating conditions were as follows: (bath solution: chromic anhydride 250 g / L, trivalent chromium 3 g / L, sulfuric acid 2.6 g / L; temperature: 52°C; nano-hard chrome accelerator addition amount: 30 ml / L; current: 4653 A; time: 150 min); during the electroplating process, the current, voltage, coating thickness, etc. were recorded. After the electroplating was completed, a 100x microscope was used for observation. The results are shown in Tables 2 and Fig.10 , the coating of the product produced in this embodiment meets the quality requirements.

[0115] Example 4

[0116] This embodiment provides a nano hard chromium accelerator, which is obtained by uniformly mixing a first solution, a second solution, a third solution, a fourth solution and a fifth solution. The preparation method includes the following steps:

[0117] Weigh 68 g of the first mixture according to a mass ratio of sodium benzenesulfinate: sodium thiosulfate = 2:1, and weigh 81.6 g of deionized water, pour the first mixture into a beaker containing 81.6 g of deionized water, and stir well to obtain a first solution;

[0118] Weigh 20 g of benzenesulfonic acid and 24 g of deionized water, pour the benzenesulfonic acid into a beaker containing 24 g of deionized water, and stir well to obtain a second solution;

[0119] Weigh 6.5 g of tartaric acid and 7.8 g of deionized water, pour the tartaric acid into a beaker containing 7.8 g of deionized water, and stir well to obtain a third solution;

[0120] Weigh 3 g of alkylphenol polyoxyethylene ether (OP-10) and 3.6 g of deionized water, pour the alkylphenol polyoxyethylene ether into a beaker containing 3.6 g of deionized water, and stir well to obtain a fourth solution;

[0121] Weigh 2.5 g of the second mixture according to a mass ratio of cobalt sulfate (particle size of 30 nm to 50 nm): silicon carbide (particle size of 30 nm to 50 nm) = 1:1, and weigh 80 ml of a 50 vol% ethanol solution, pour the second mixture into a beaker containing 80 ml of the 50 vol% ethanol solution, and stir well to obtain a fifth solution with a pH value of 9 to 10;

[0122] The first solution, the second solution, the third solution, the fourth solution and the fifth solution were poured into the same beaker and stirred evenly to obtain about 253 ml of nano hard chromium accelerator.

[0123] Take the nano-hard chrome accelerator of this example to carry out the nine-square Hastelloy slot test piece experiment. For the experimental results, please refer to Fig.11 and Fig.12 In this embodiment, there are only three positions on the back of the Hastelloy plate without coating, and the coating dispersion distance on the front of the Hastelloy plate is relatively long, and there is a small black surface at the end of the coating dispersion.

[0124] The nano-hard chrome accelerator of this embodiment was used to perform hard chrome electroplating on the hydraulic oil rod product. The electroplating conditions were as follows: (bath solution: chromic anhydride 250 g / L, trivalent chromium 3 g / L, sulfuric acid 2.6 g / L; temperature: 52°C; nano-hard chrome accelerator addition amount: 30 ml / L; current: 4653 A; time: 150 min); during the electroplating process, the current, voltage, coating thickness, etc. were recorded. After the electroplating was completed, a 100x microscope was used for observation. The results are shown in Tables 2 and Fig.13 , the coating of the product produced in this embodiment meets the quality requirements.

[0125] Comparative Example 1

[0126] This comparative example adopts the currently used commercially available chrome plating additive (CK chrome plating additive), and the confirmed formula dosage is 50-200g of organic acid salt, 10-50g of organic acid, 1-10g of buffer, and 0-5g of wetting agent, wherein the organic acid salt includes one of sodium sulfonate, sodium acetate, sodium aminosulfonate, sodium aminoacetate, and sodium tannate, or any combination of several of them; the organic acid includes one of citric acid, methanesulfonic acid, acetic acid, and aminosulfonic acid, or any combination of several of them, and deionized water in the organic acid salt, organic acid, buffer, and wetting agent all accounts for 60wt%.

[0127] The chrome plating additive of this comparative example was used to conduct a nine-square Hastelloy slot test. For the test results, please refer to Fig.14 and Fig.15 There are only three positions on the back of the Hastelloy plate in this comparative example without coating, and the coating dispersion distance on the front of the Hastelloy plate is relatively long, and there is a small area of ​​black surface at the end of the coating dispersion.

[0128] The chrome plating additive of this comparative example was used to perform hard chrome electroplating on the hydraulic oil rod product. The electroplating conditions were as follows: (bath solution: chromic anhydride 250g / L, trivalent chromium 3g / L, sulfuric acid 2.6g / L; temperature: 52°C; chrome plating additive addition amount: 30ml / L; current: 4653A; time: 150min); during the electroplating process, the current, voltage, coating thickness, etc. were recorded. After the electroplating was completed, a 100x microscope was used for observation. The results are shown in Tables 2 and Fig.16 .

[0129] The above hydraulic oil rod products are all products of the same batch and model with the same size.

[0130] Table 2

[0131]

[0132] From the experimental results of the nine-grid Hastelloy slot test pieces of Examples 1 to 4, it can be seen that Example 1 is a formula with relatively poor effect; and from the experimental results of the nine-grid Hastelloy slot test pieces of Example 1 and Comparative Example 1, it can be seen that the number of points of the coating on the back of the Hastelloy sheet in Example 1 is increased by 2 compared with Comparative Example 1, and the hole surface and appearance of the coating on the Hastelloy sheet are significantly improved, while the black surface and shadow are significantly reduced, and the length of the dispersion on the front side of the Hastelloy sheet in Example 1 is significantly increased compared with Comparative Example 1, and the black surface and shadow at the end of the dispersion are significantly reduced; it can be seen that the nano hard chromium accelerator of the present invention can significantly improve the coating quality and electroplating efficiency.

[0133] In the nine-grid Hastelloy slot test piece experiment, Examples 2 to 4 can ensure that the nine points on the back of the Hastelloy sheet are coated, and Examples 2 to 3 can also ensure that there is no obvious shadow at the dispersed end of the Hastelloy sheet, and Example 2 can also ensure that the coatings at the nine points on the back of the Hastelloy sheet have larger hole surfaces, and Example 2 can also achieve a deposition rate of 0.01 to 0.012 mm / 15 min in the first 15 minutes of electroplating, a current efficiency of 23 to 25.9%, and a coating hardness of 1250 HV.

[0134] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and the present invention is also intended to include these modifications and modifications.

Claims

1. A nano hard chrome accelerator, characterized in that: The first solution, the second solution, the third solution, the fourth solution and the fifth solution are uniformly mixed to obtain; The first solution includes 40 g to 80 g of a first mixture and 60 wt % of deionized water, wherein the first mixture includes sodium benzenesulfinate and sodium thiosulfate in a mass ratio of 2:1; The second solution includes 10 g to 50 g of benzenesulfonic acid and 60 wt % of deionized water; The third solution comprises 2 g to 8 g of tartaric acid and 60 wt % of deionized water; The fourth solution comprises 1 g to 5 g of alkylphenol polyoxyethylene ether and 60 wt % of deionized water; The fifth solution includes 0.5g to 3g of the second mixture and 60wt% ethanol solution, the concentration of the ethanol solution is 50vol%, the second mixture includes nano-cobalt sulfate and nano-silicon carbide in a mass ratio of 1:1, and the particle size of the nano-cobalt sulfate and the particle size of the nano-silicon carbide are 30nm to 50nm.

2. The nano hard chromium accelerator according to claim 1, characterized in that The mass of the first mixture is 55g-70g, the mass of the benzenesulfonic acid is 20g-40g, the mass of the tartaric acid is 3.5g-6.5g, the mass of the alkylphenol polyoxyethylene ether is 1g-3g, and the mass of the second mixture is 0.5g-2.5g.

3. The nano hard chromium accelerator according to claim 1, characterized in that The mass of the first mixture is 65g-70g, the mass of the benzenesulfonic acid is 20g-25g, the mass of the tartaric acid is 5g-6.5g, the mass of the alkylphenol polyoxyethylene ether is 2g-3g, and the mass of the second mixture is 1.5g-2.5g.

4. The nano hard chromium accelerator according to claim 1, characterized in that: The mass of the first mixture is 65 g, the mass of the benzenesulfonic acid is 25 g, the mass of the tartaric acid is 6 g, the mass of the alkylphenol polyoxyethylene ether is 2 g, and the mass of the second mixture is 2 g.

5. The nano hard chromium accelerator according to claim 1, characterized in that: The mass of the first mixture is 70 g, the mass of the benzenesulfonic acid is 20.5 g, the mass of the tartaric acid is 5 g, the mass of the alkylphenol polyoxyethylene ether is 3 g, and the mass of the second mixture is 1.5 g.

6. A method for preparing the nano hard chromium accelerator according to any one of claims 1 to 5, characterized in that: The following steps are involved: Weigh 40 wt% of the first mixture according to the ratio and add it into 60 wt% of deionized water to fully dissolve and stir evenly to obtain a first solution; Weigh 40 wt % of benzenesulfonic acid according to the ratio and add it to 60 wt % of deionized water to fully dissolve and stir evenly to obtain a second solution; Weigh 40 wt % of tartaric acid according to the ratio and add it into 60 wt % of deionized water to fully dissolve and stir evenly to obtain a third solution; Weigh 40 wt % of alkylphenol polyoxyethylene ether according to the ratio and add it into 60 wt % of deionized water to fully dissolve and stir evenly to obtain a fourth solution; Weigh 40 wt % of the second mixture according to the ratio and add it into a 60 wt % ethanol solution to fully dissolve and stir evenly to obtain a fifth solution with a pH value between 9 and 10; The first solution, the second solution, the third solution, the fourth solution and the fifth solution are mixed and stirred uniformly to obtain a nano hard chromium accelerator.

7. Use of the nano hard chrome accelerator as claimed in any one of claims 1 to 5, characterized in that: Used in hard chrome plating.

8. The nano hard chromium accelerator according to claim 7, characterized in that: The application method comprises the following steps: adding the nano hard chrome accelerator into a hard chrome plating tank filled with hard chrome plating solution.

9. The nano hard chromium accelerator according to claim 8, characterized in that: The dosage of the nano hard chrome accelerator is 30 ml / L.

10. The use of the nano hard chrome accelerator according to claim 8, characterized in that: The hard chrome plating solution comprises chromic anhydride, trivalent chromium and sulfuric acid.

Citation Information

Patent Citations

  • Trivalent chromium sulfate plating solution and preparation method thereof

    CN101665960A

  • Electrochromism solution for gridiron and electrochromism method thereof

    CN106167908A

  • Trivalent chromium coating and preparation method thereof

    CN107419310A

  • Micro-crack hard-chromium composite coating and preparation method thereof

    CN109023488A

  • High-brightness durionise additive and production method thereof

    CN109457277A